New media and the digitized paranormal: instrumentation, affective atmospheres, and the production of history in Chile. (31st March 2021) - Espírito Santo, Diana; Barceló, Gonzalo
Abstract: In the last decade in Chile, an increasing amount of paranormal investigation companies have carried out ghost tours in patrimonial and historical places, using diverse technologies to penetrate into the history of sites. We ethnographically and analytically explore two related questions. First, we ask what paranormal instrumentation does to collective memory and to history. We argue that these 'registers' of the paranormal create 'affective atmospheres', namely from the forms of indeterminacy embedded in the functioning and performance of the apparatuses. Our argument is that these machines are mechanisms for the creation of a new history, one that is apprehended affectively. Second, in the context of an explosion of adherence in Chile to forms of new media, we employ the notion of 'dark media' to illustrate that online material posted by paranormal researchers appears to escape any form of mediational understanding, feeding at once the public's perceptive and affective dispositions. Abstrait: Nouveaux médias et numérisation du paranormal : instrumentation, atmosphères affectives et réécriture de l'Histoire au Chili Résumé Au Chili, depuis une dizaine d'années, un nombre croissant d'agences d'enquêtes paranormales organisent des visites de sites patrimoniaux et historiques prétendument hantés, ayant recours à diverses technologies pour pénétrer dans l'histoire de ces lieux. L'autrice procède à une exploration ethnographique et analytique de deux questions liées. En premier lieu, elle s'interroge sur les effets de l'instrumentation paranormale sur la mémoire collective et l'Histoire. Elle avance que ces « registres » du paranormal créent des « atmosphères affectives » à travers les formes d'indétermination qui caractérisent le fonctionnement et la performance des instruments utilisés. Ces machines constituent des mécanismes pour la création d'une nouvelle histoire, appréhendée du point de vue affectif. En second lieu, dans le contexte du succès fulgurant des nouveaux médias au Chili, la notion de « médias noirs » illustre le constat que le contenu en ligne publié par les paranormalistes semble échapper à toute forme de compréhension médiationnelle, nourrissant immédiatement les tempéraments perceptifs et affectifs du public.